Obtenção e caracterização de plataformas fotoeletroquímicas à base de tantalato de sódio (NaTaO3) e tantalato de cálcio e bismuto (CaBi2Ta2O9) visando o desenvolvimento de imunossensores aplicáveis para a detecção de troponina I (cTnI) - CALDAS, Greicy Kelly Cerqueira (2023)
In this work, two photoelectrochemical platforms based on ceramic materials specifically sodium tantalate (NaTaO3) and calcium tantalate and bismuth (CaBi2Ta2O9), for detection of the cardiac troponin I (cTnI) biomarker in Human serum samples were development.The first platform was formed by bismuth-doped NaTaO3 (NaTaO3-Bi) sensitized with sulfur-doped graphitic carbon nitride (S-g-C3N4) and bismuth iodide oxide (BiOI). The second platform was built based on CaBi2Ta2O9 and sensitized with bismuth oxyiodides (BiOI/Bi4O5I2/Bi5O7I). Both platforms were used for zero-biased photoelectrochemical immunosensing of cardic troponin I (cTnI) biomarker. The spectroscopic, structural, morphological, and compositional characteristics of the photoelectrochemical (PEC) materials were evaluated by Raman and Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), and energy-dispersive X-ray spectroscopy (EDS). Electrochemical Impedance Spectroscopy (EIS) measurements were performed under the incidence and absence of light to investigate the effects of photons on the charge transfer resistance of the photoelectrochemical platform. Both platforms were incubated with cTnI blinding (anti-cTnI) and named as anti-cTnI/BiOI/S- g-C3N4/Bi-NaTaO3/FTO and anti-cTnI/BiOI/Bi4O5I2/Bi5O7I/CaBi2Ta2O9/FTO immunosensors. cTnI for detection of the cTnI biomarker. The anti-cTnI/BiOI/S-g- C3N4/Bi-NaTaO3/FTO immunosensor showed a linear response in the concentration range of 0.001-50 ng mL-1 , with a detection limit of 0.1 pg mL-1 for the cTnI biomarker. The anti-cTnI/BiOI/Bi4O5I2/Bi5O7I/CaBi2Ta2O9/FTO immunosensor showed linear ranges of 0.001-200 ng mL-1 , with detection limits of 0,17 pg mL-1 . The immunosensors applied to a human serum sample showed recovery values between 95,6 and 108%. The two immunosensors showed selectivity against interfering species found in human serum samples.